已知关于 $x$ 的方程 $x^2-(2 \mathrm{~m}-1) x+\mathrm{m}^2=0$ 的两实数根为 $x_1, x_2$, 若 $\left(x_1+1\right)\left(x_2+1\right)=3$, 则 $\mathrm{m}$ 的值为
$ \text{A.} $ $-3$ $ \text{B.} $ $-1$ $ \text{C.} $ $-3$ 或$1$ $ \text{D.} $ $-1$ 或$3$
【答案】 A

【解析】 $\because$ 方程有两实数根, $\therefore$ 判别式 $(2 \mathrm{~m}-1)^2-4 \mathrm{~m}^2 \geqslant 0$, 解得 $\mathrm{m} \leqslant \frac{1}{4}, \because$ $\left(\boldsymbol{x}_1+1\right)\left(\boldsymbol{x}_2+1\right)=\boldsymbol{x}_1 \boldsymbol{x}_2+\boldsymbol{x}_1+\boldsymbol{x}_2+1=3$, 由韦达定理知 $\boldsymbol{x}_1 \boldsymbol{x}_2=\mathrm{m}^2, \boldsymbol{x}_1+\boldsymbol{x}_2=2 \mathrm{~m}-1, \quad \therefore \mathrm{m}^2+2 \mathrm{~m}-1+1=3$, 解得 $m_1=1$ (舍去), $m_2=-3$, 故选 $A$.
系统推荐